Cytomorphological Pattern, Evaluation of Serum Adenosine Deaminase (ADA) Level and Clinical Presentation of Peripheral Lymph Node Tuberculosis – An Observational Study - Sarkar, Nirmal Kanti; Rahman, Md Ashadur; Roy, Moumita; Akter, Jesmin; Hossain, Mohammad Mosharaf; Islam, Md Serazul; Mujahid, Abdullah Al (Chest & Heart Journal, 2021)
Background: Lymphadenitis is the most common form of extrapulmonary TB. Fine needle aspiration cytology (FNAC) is the most commonly used diagnostic tool. This study observed the cytomorphological pattern, serum adenosine deaminase (ADA) level and clinical presentation of lymph node TB. Methods: We conducted a cross-section, observational study at the 250-Bedded T.B Hospital, Shyamoli, Dhaka, Bangladesh between January 2019 -January 2020 among the patients with peripheral lymphadenopathy and compatible clinical features favoring tuberculous etiology attending at the outpatient and inpatient department. Patients were categorized in three groups according to the lymph node FNAC pattern. Clinical presentation and radiological findings were evaluated and serum ADA level was estimated. Any association between lymph node cytology and serum ADA level was sought. Results: Total 36 patients were enrolled in the study. Among them 75% were female and the mean age was 33.5±14.6 years. All the patients had cervical lymphadenopathy, and 83.3% had matted lymph nodes. Eighty six percent patients had high serum ADA level above cut-off value. The most common cytomorphological pattern observed in lymph node FNAC was epithelioid granuloma with caseous necrosis (58.3%). There was significant relationship between lymph node cytomorphological pattern and serum ADA level (p<0.05). Conclusions: Tuberculous lymphadenitis is more common among female than male. Most common site of lymph node TB is cervical region, and epithelioid granuloma with caseous necrosis is the most frequently observed cytological pattern. Serum ADA is shown to have a potential role to support the diagnosis of tuberculous lymphadenitis. Chest Heart J. 2020; 44(2) : 61-67